Laparoscopic removal of a giant middle ureteral stone: A case report and review of literature - Yasseri, Alimohammad Fakhr (Ann Med Surg (Lond), 2020)
Giant ureteral calculi stones defined as larger than 5 cm in length or circumference. Although many giant ureteral stones have been reported, the laparoscopic removal of these stones is rare. A 45-year-old male patient presented to our clinic with right flank pain and discomfort from 6 months ago. Abdominopelvic computed tomographic scan showed a giant left middle ureteral stone. On the first stage laparoscopic ureter lithotomy was performed with 3 ports and the stone was extracted from 12 mm port successfully. We used transperitoneal laparoscopic approach in the full lateral decubitus position. three trocars were placed: one camera 11-mm port was placed at the level of the umbilicus on the lateral border of the rectus muscle, a 5-mm port was placed in the midline below the umbilicus, and a 12-mm port was at the superior border of the rectus muscle. The extracted stone size was 6.5*1.7 cm with 33 gm in weight. Due to the advantages of laparoscopic ureter lithotomy in giant ureteral stones and its feasibility to perform in a single session, we could suggest this minimally invasive treatment as a first choice in this group of patients.